2019
DOI: 10.3389/fnins.2019.01247
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Acid-Sensing Ion Channel 1b in the Development of Acid-Induced Chronic Muscle Pain

Abstract: Acid-sensing ion channels (ASICs) are important acid sensors involved in neural modulation in the central nervous system and pain-associated tissue acidosis in the peripheral system. Among ASIC subtypes, ASIC1b is the most selectively expressed in peripheral sensory neurons. However, the role of ASIC1b is still elusive in terms of its functions and expression profile. In this study, we probed the role of ASIC1b in acid-induced muscle pain in Asic1b-knockout (Asic1b–/–) and Asic1b-Cre transgenic (Asic1bCre) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 36 publications
5
41
0
Order By: Relevance
“…This demonstrated for the first time that ASIC1b-containing channels in rodent nociceptors, as opposed to the splice isoform ASIC1a, are important for peripheral analgesia. More recent work using an ASIC1b knockout animal confirmed the role of this subtype in peripheral pain sensing [78]. In this model, peripheral injection of mambalgin had no effect on acid-induced hyperalgesia in ASIC1b knockout mice.…”
Section: Uncovering New Analgesic Targets Using Animal Toxinsmentioning
confidence: 55%
“…This demonstrated for the first time that ASIC1b-containing channels in rodent nociceptors, as opposed to the splice isoform ASIC1a, are important for peripheral analgesia. More recent work using an ASIC1b knockout animal confirmed the role of this subtype in peripheral pain sensing [78]. In this model, peripheral injection of mambalgin had no effect on acid-induced hyperalgesia in ASIC1b knockout mice.…”
Section: Uncovering New Analgesic Targets Using Animal Toxinsmentioning
confidence: 55%
“…Local injection of the same dose (~0.1 mg/kg) also produced a significant analgesic effect on acute heat pain and reversed carrageenan-induced inflammatory hyperalgesia via ASIC1b ( Diochot et al., 2012 ). An intravenous administration 15-30 pmol/mouse (~0.005–0.01 mg/kg dose) of mambalgin-1 was reported to produce a significant analgesic effect in models of acid-induced mechanical hyperalgesia, thus confirming ASIC1b as a perspective pharmacological target on peripheral neurons ( Chang et al., 2019 ).…”
Section: Perspectives In Therapeutic Developmentmentioning
confidence: 94%
“…In particular, interesting results were obtained in showing that ASIC1a subtypes play an important role in retinal activity ( Ettaiche, 2006 ). Also, due to the successful selective inhibition of the ASIC1a subtype, it was shown that ASIC1b is involved in the development of muscle pain ( Chang et al., 2019 ) and that the ASIC3 subtype is responsible for postoperative pain ( Deval et al., 2011 ).…”
Section: Natural Ligands Of Acid-sensing Ion Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Classified as a specific inhibitor of ASIC1a, the most abundant acid-sensing ion channel, the toxin π-TRTX-Pc1 demonstrated an effective analgesic effect comparable to morphine in rat models of acute pain ( Mazzuca et al., 2007 ). Recently, PcTx1 was also reported as a valuable tool for understanding the functional role of ASIC2a heteromeric channels (ASIC1a/2a) ( Liu et al., 2018 ) and had no effect on acid-induced transient or chronic hyperalgesia in a mouse model of fibromyalgia ( Chang et al., 2019 ).…”
Section: Promising Animal Toxins In Preclinical Stage and Clinical Trmentioning
confidence: 99%